Time Since Migration and HIV Risk Behaviors Among Puerto Ricans Who Inject Drugs in New York City. (6th June 2016) - Gelpí-Acosta, Camila; Pouget, Enrique R.; Reilly, Kathleen H.; Hagan, Holly; Neaigus, Alan; Wendel, Travis; Marshall, David M.
ABSTRACT: Background : Among people who inject drugs (PWID) in the United States, those who initiated drug injection in Puerto Rico (immigrant Puerto Rican PWID) engage in more injection and sexual risk behaviors, and have higher HIV incidence than non-Hispanic whites. Objective : Understand the persistence of these HIV behaviors. Methods : In a cross-sectional study conducted in New York City (NYC) in 2012 (National HIV Behavioral Surveillance), PWID aged ≥18 years were recruited using Respondent-Driven Sampling, interviewed, and tested for HIV. Participants were categorized into 5 different groups: (1) US-born non-Hispanic PWID, (2) US-born Puerto Rican PWID, (3) recent immigrant Puerto Rican PWID (≤3 years in NYC), (4) medium-term immigrant Puerto Rican PWID (>3 and ≤10 years in NYC), and (5) long-term immigrant Puerto Rican PWID (>10 years in NYC). We examined the relationship between time since migrating on sexual and injection risk behaviors among immigrant Puerto Rican PWID, compared with U.S.-born Puerto Rican PWID and US-born non-Hispanic PWID. Adjusted odds ratios (aOR) and 95% confidence intervals (95% CI) were estimated using logistic regression. Results : A total of 481 PWID were recruited. In adjusted analyses using US-born non-Hispanic PWID as the comparison group, syringe sharing was significantly more likely among medium-term immigrants; and unprotected sex with casual partners was more likely among recent and long-term immigrants. Conclusions : The risk-acculturation process for immigrant Puerto Rican PWID may be nonlinear and may not necessarily lead to risk reduction over time. Research is needed to better understand this process.